The crime of electronic incitement to undermine the constitutional order through social media - Abdul Rahim, Ahmed Hammad Abdullah; Ahmed, Abker Ali Abdul Majeed; Yusuf, Alnmash Abdul Rahman Mohammed (Journal of Economic, Administrative and Legal Sciences, 2017)
In recent years the world witnessed a notable development in cognitive sciences, particularly, after the internet discovering which let the information flow easily overall the world, and that to lead to electronic crime – this development has accompanied by multi mediums social connections which enabled people to penetrate the web sides easily to violate a privacy the social media is used among students and youth for social connection but , on their hand is used by a negative way and it is used by apolitical avidities group to push over the constitutional regime which lead to disorders among the Islamic countries.This research tackles the electronic inciting to undermine the constitutional regime through the social mass media. And there are acts related to this issue, such as Sudanese criminal act for 1993, Sudanese proving act for 1994, and Sudanese informational crimes act for 2007.
Keywords: electronic incitement; undermining; the constitutional system; social media